2002
DOI: 10.1108/01435120210697441
|View full text |Cite
|
Sign up to set email alerts
|

Management issues in library networking: focus on a pilot library networking project in Ghana

Abstract: Discusses the management issues involved in library networking, using GILLDDNET, the DANIDA/IFLA sponsored Ghana Interlibrary Lending and Document Delivery Trial Project as a reference point in the discussion. There is an attempt to apply the management principles that Urwick outlined decades ago in the Elements of Management to this project. The challenges and the successes of the project are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Especially in the 1980s and 1990s, a rapid increase in the number and cost of books and journals, combined with severe constraints placed on library budgets -especially in academic libraries -became a worldwide phenomenon, further exacerbated in those countries with volatile currency units (Hooper, 1990). The consequences of these problems were obsolete equipment, untrained personnel, out-of-date collections (Martey, 2002) and the resultant imperative to downsize/right-size, together with political pressure to collaborate (Kopp, 1998). It became imperative to find ways of making the most efficient use of the resources available by reducing duplication of book and journal purchases, especially on a regional basis, and optimizing interlibrary loan traffic to ensure the most efficient and effective use of those materials already available within the country.…”
Section: Alliance Forming For Information Provisionmentioning
confidence: 99%
“…Especially in the 1980s and 1990s, a rapid increase in the number and cost of books and journals, combined with severe constraints placed on library budgets -especially in academic libraries -became a worldwide phenomenon, further exacerbated in those countries with volatile currency units (Hooper, 1990). The consequences of these problems were obsolete equipment, untrained personnel, out-of-date collections (Martey, 2002) and the resultant imperative to downsize/right-size, together with political pressure to collaborate (Kopp, 1998). It became imperative to find ways of making the most efficient use of the resources available by reducing duplication of book and journal purchases, especially on a regional basis, and optimizing interlibrary loan traffic to ensure the most efficient and effective use of those materials already available within the country.…”
Section: Alliance Forming For Information Provisionmentioning
confidence: 99%
“…With advances in networking, Schneider's (2002) paper which examines membership of regional library systems is interesting, for a study showed that librarians valued their local personal contacts. Martey (2002b) discusses the management issues experienced in library networking in Ghana.…”
Section: Managing Collaboration Partnerships and Consortiamentioning
confidence: 99%
“…There has, so far, been only one bold attempt to set up a library consortium in Ghana (Martey, 2002). Ghanaian academic librarians have, however, not given up on consortia.…”
Section: Introductionmentioning
confidence: 96%